Tribological Testing of Hemispherical Titanium Pin Lubricated by Novel Palm Oil : Evaluating Anti-Wear and Anti-Friction Properties - Norzahir, Sapawe; Syahrullail, Samion; Mohd Izhan, Ibrahim; Md Razak, Daud; Azli, Yahya; Muhammad Farhan, Hanafi (BioMed Central Ltd., 2017)
In this study, the properties of hip implant material and lubricants were examined using a pin on disc apparatus, to compare the effect of metal-on-metal (MoM) contact with a bio-lubricant derived from palm oil. The behaviour of the lubricants was observed during the experiments, in which a hemispherical pin was loaded against a rotating disc with a groove. A titanium alloy was used to modify the hemispherical pin and disc. Before and after the experiments, the weight and surface roughness were analysed, to detect any degradation. The results were compared according to the different kinematic viscosities. The wear rates and level of friction with each lubricant were also examined. The lubricant with the highest viscosity had the lowest frictional value. Therefore, developing suitable lubricants has the potential to prolong the lifespan of prostheses or implants used in biomedical applications. The experiments collectively show that lubricants derived from palm oil could be used as efficient bio-lubricants in the future.